THE INFLUENCE OF LEVERAGE AND COMPANY SIZE ON PROFITABILITY (Study on Manufacturing Companies Listed in Indonesia Stock Exchange) - Mahesa Pangalila, Jovan Leonard (Jurnal Ilmiah Mahasiswa FEB, 2020)
This study aims to determine and analyse the effect of leverage and company size on profitability in the manufacturing companies listed on the Indonesia Stock Exchange. The variables studied include leverage and company size. Where these two determinants are taken from the gap of previous research which gives different results. This type of research is explanatory research, which means explaining whether there is an influence between the independent variables and the dependent variable through hypothesis testing. The data used is secondary data. The sampling method used in this study is purposive sampling, which is applying certain criteria that eliminate the population in accordance with research requirements. Hypothesis testing is done using multiple regression analysis which was preceded by a classic assumption test consisting of normality test, heteroscedasticity test, multicollinearity test, and autocorrelation test. The results of the data analysis show that leverage significantly affects profitability. While company size has no significant effect on profitability.Keywords: Profitability, Leverage, and Company Size